Investigation of CdSe and ZnSe as Potential Back Surface Field Layers for CdTe‐Based Solar Cells: A Study from First Principles Calculations. Issue 3 (19th January 2023) - Ray, Subhasmita; Tarafder, Kartick
Abstract: A class of II–VI semiconductors, especially CdTe, is a highly photo‐reactive compound that would be suitable for photovoltaic applications. However, being a highly resistive material, CdTe produces considerable contact resistance and drastically reduces the efficiency of photovoltaic devices. Introducing a back surface field layer at the contact region may significantly improve the device's performance. This work investigates the suitability of using ZnSe and CdSe layer as a back‐surface‐field layer in CdTe‐based solar cells through accurate electronic structure calculations using the hybrid‐density functional theory method. The calculations show that both ZnSe/CdTe and CdSe/CdTe behave as type‐II heterojunctions with band gaps of 2.0 and 1.1 eV, respectively. The Mulliken electronegativity method is used to determine the correct band edge positions concerning the vacuum level for all the pristine semiconductors and their interfaces. Calculation shows that a significant charge redistribution in the interface leads to the formation of an effective local field near the contact region for both ZnSe/CdTe and CdSe/CdTe heterostructures. This local field may help to separate the photogenerated electron–hole pairs in the active layer by pushing the opposite charges into the two different sections of the heterojunction. Additionally, the heterojunctions also exhibit better light‐absorption characteristics in the visible light range. Abstract : Through the hybrid‐DFT calculations, this work examines the suitability of CdSe and ZnSe as back‐surface‐field layers for the CdTe solar cells. Investigation shows that type‐II heterojunctions ZnSe/CdTe and CdSe/CdTe exhibit improved light absorption behavior. Large band offsets are estimated in these systems, which may help to separate electron–hole pairs and efficiently transport the photogenerated charge carriers to the back contacts.